Comparison of psychological functioning in children and their mothers living through a life-threatening and non life-threatening chronic disease: A pilot study. (June 2016) - Graziano, Sonia; Rossi, Angela; Spano, Barbara; Petrocchi, Michela; Biondi, Gianni; Ammaniti, Massimo
Childhood chronic illness is a potential source of distress and can be a traumatic experience both for the child and for the family. Several studies highlighted the importance of integrating psychosocial care and standard medical practice in the child's care. The current pilot study is the first investigation that compared distress in children and their mothers living through a life-threatening illness (cancer) and a non life-threatening (juvenile rheumatoid arthritis) chronic disease. Findings show that there are differences in the psychological functioning in children with respect to age. Moreover, the presence of posttraumatic stress symptoms in mothers of children with cancer seems to be a possible key to understanding the psychological response in this specific population.